A phosphotungstic acid-based solid electrolyte material and a preparation method and application thereof

CN123018108APending Publication Date: 2026-10-30LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611324691.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0010]本发明旨在解决Keggin型磷钨酸基固态电解质综合性能不足的技术难题,特别是离子电导率、力学柔韧性与冷压成型性三者难以兼顾的矛盾,提供了一种磷钨酸基固态电解质材料及其制备方法和应用

Benefits of technology

[0047]本发明提供的制备方法,通过溶液法在温和条件下完成Al3+和Zr4+对Keggin骨架中W6+的异价共取代,取代反应在60℃~90℃的水相体系中即可进行,避免了传统高温固相反应所需的数百度高温,有效防止了高温处理可能引起的Keggin骨架坍塌、相分离和元素挥发等问题,确保了产物结构的完整性和一致性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018108A_ABST
    Figure CN123018108A_ABST
Patent Text Reader

Abstract

The application relates to a phosphotungstic acid-based solid electrolyte material and a preparation method and application thereof. 3+ and Zr 4+ heterovalence co-doped Keggin type phosphotungstic acid anion nanocrystals; the intermediate transition layer comprises a charge reconstruction region and a composition gradient interface induced by Al 3+ and Zr 4+ heterovalence co-doping; the shell functional layer comprises an organic-inorganic hybrid layer in which organic plastic-lubricating bifunctional components and oxide solid electrolytes are interpenetrated; the application utilizes Al 3+ and Zr 4+ heterovalence co-substitution to create lithium vacancies through charge compensation, combines Al 3+ small radius contraction and Zr 4+ large radius expansion of the synergistic lattice distortion and the stable effect of the Zr-O strong bond on the skeleton, so that the material has high conductivity and low Young's modulus, and when applied to a full solid-state lithium battery, the interface impedance can be significantly reduced, and the cycle stability and safety of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and in particular to a phosphotungstic acid-based solid electrolyte material, its preparation method, and its application. Background Technology

[0002] The performance of solid-state electrolytes directly determines the safety, energy density, and cycle life of all-solid-state batteries, making it a current research hotspot and challenge in the field of new energy materials. Among numerous solid-state electrolyte systems, Keggin-type polyoxometalates are considered to be promising emerging solid-state electrolyte systems due to their unique ion transport channel structure and excellent plasticity. Lithium phosphotungsten oxide, for example, can achieve a relative density of over 90% under 300 MPa pressure, demonstrating good potential for cold-pressing.

[0003] To improve the ionic conductivity of phosphotungstic acid-based solid electrolytes, researchers have explored various modification strategies, including phosphorus pentoxide doping, transition metal ion substitution, and composite formation with oxide solid electrolytes such as lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium lanthanum titanium oxide, and lithium aluminum titanium phosphorus oxide. Regarding single-metal substitution, single substitution with elements such as copper, titanium, and vanadium has also been reported. However, the above studies are limited to the substitution modification of single-valence metal ions; the heterovalent co-substitution strategy, which simultaneously introduces two metal ions with valence states different from hexavalent tungsten ions into the Keggin-type phosphotungstic acid framework, has not yet been systematically studied. Existing techniques mainly optimize performance from the perspective of structural distortion, failing to fully understand and utilize the charge compensation effect produced by heterovalent substitution.

[0004] Existing Keggin-type phosphotungstic acid-based solid electrolytes still have the following shortcomings in terms of overall performance.

[0005] First, the Young's modulus is too high, resulting in excessive material rigidity. The lack of a flexible buffer phase between the pure inorganic Keggin framework and the direct contact between rigid particles lead to a Young's modulus of several gigapascals. This excessively high modulus results in poor interfacial contact between the electrolyte and the electrode, significantly increasing the interfacial impedance. Furthermore, the material is prone to cracking when bent, making it difficult to meet the mechanical performance requirements of solid electrolytes for flexible electronic devices.

[0006] Secondly, cold pressing has a narrow forming window and poor process adaptability. To obtain a higher relative density, high forming pressure is usually required, but high-pressure forming introduces residual stress and microcracks, affecting the structural integrity of the electrolyte and ion transport efficiency. More importantly, excessive compression can block the ion transport channels between Keggin units, causing the ionic conductivity to decrease instead of increase, creating an irreconcilable contradiction between density and conductivity.

[0007] Third, the ionic conductivity is too low to meet practical application requirements. The existing Keggin-type phosphotungstic acid-based solid electrolyte has an ionic conductivity of only about one millisiemens per centimeter at room temperature, significantly lower than the conductivity levels of liquid electrolytes, which are generally above ten negative square siemens per centimeter. Single-valent metal substitution has limited effect on improving conductivity, while heterovalent substitution strategies, which can create a large number of lithium vacancies through charge compensation effects and thus significantly increase carrier concentration, have not yet been systematically studied. This has become a key bottleneck restricting further improvements in the material's conductivity.

[0008] Fourth, there is a lack of targeted heterovalent co-substitution strategies. In existing technologies, trivalent aluminum ions have a small ionic radius and strong Lewis acidity, while tetravalent zirconium ions have a large ionic radius and a high coordination number. The two have significant complementary and synergistic potential in structural regulation. Aluminum ions tend to occupy the apex position of the Keggin framework, while zirconium ions tend to occupy the bridging position. This differentiated occupation is expected to create richer and more diverse lithium-ion hopping pathways than a single substitution system. Simultaneously, the substitution of hexavalent tungsten ions by low-valent aluminum and zirconium ions can create a large number of lithium vacancies while maintaining charge balance, thereby increasing carrier concentration and reducing ion migration activation energy. However, this synergistic effect of heterovalent co-substitution has not yet been recognized and utilized in existing technologies.

[0009] In summary, Keggin-type phosphotungstic acid-based solid electrolytes currently face multiple problems, including low ionic conductivity, high Young's modulus, narrow cold pressing window, and lack of effective heterovalent co-substitution strategies. The contradiction between ionic conductivity, mechanical flexibility, and formability is particularly prominent, and new material design ideas are urgently needed to overcome these performance bottlenecks. Summary of the Invention

[0010] This invention aims to solve the technical problem of insufficient comprehensive performance of Keggin-type phosphotungstic acid-based solid electrolytes, especially the contradiction between ionic conductivity, mechanical flexibility and cold pressing formability. It provides a phosphotungstic acid-based solid electrolyte material, its preparation method and application.

[0011] To achieve the above objectives, in a first aspect, the present invention provides a phosphotungstic acid-based solid electrolyte material having a core-shell structure, comprising:

[0012] Kernel, the kernel being Al 3+ and Zr 4+ Heterovalent co-doped Keggin-type phosphotungstic acid anion nanocrystals.

[0013] An intermediate transition layer, which covers the surface of the core and comprises Al 3+ and Zr 4+Heterovalent co-doping induced charge reconstruction region and composition gradient interface.

[0014] The outer shell functional layer covers the surface of the intermediate transition layer and includes an organic-inorganic hybrid layer in which organic plasticizer-lubricant bifunctional components and oxide solid electrolyte interpenetrate.

[0015] Preferably, the general chemical composition formula of the phosphotungstic acid-based solid electrolyte material is as follows.

[0016] (1-α)[Li x H (3-x) Al a Zr b PW 12-(a+b) O 40 ·mH2O·nL·zD]+α[Oxide].

[0017] Among them, Li x H (3-x) Al a Zr b PW 12-(a+b) O 40 ·mH2O is Al 3+ and Zr 4+ The general chemical formula for heterovalent co-doped Keggin-type phosphotungstic acid anionic nanocrystals is 0.5≤x≤4.0, 0.05≤a≤1.5, 0.05≤b≤1.5, 0.1≤a+b≤2.5, and 0≤m≤8.

[0018] L is an organic plasticizer-lubricant dual-function component, and n represents the mass ratio of L to Keggin-type phosphotungstic acid anionic nanocrystals, where 0.05 ≤ n ≤ 0.3.

[0019] D represents the interstitial compound, z represents the molar ratio of D to the Keggin-type phosphotungstic acid anionic nanocrystals, and 0.01≤z≤0.3.

[0020] Oxide represents an oxide solid electrolyte, where 0.05 ≤ α ≤ 0.5.

[0021] More preferably, the particle size Dv50 of the Keggin-type phosphotungstic acid anion nanocrystals is 5nm to 20nm.

[0022] The organic plasticizer-lubricant bifunctional component includes one or more of polyethylene glycol (PEG), polyethylene oxide (PEO), or polypropylene oxide (PPO).

[0023] The interstitial compound includes one or more of P2O5, SiO2, or B2O3.

[0024] The oxide solid electrolyte includes one or more of LATP, LLZO, or TA-LLZTO.

[0025] Preferably, the room temperature ionic conductivity of the phosphotungstic acid-based solid electrolyte material is 1×10⁻⁶. -2 S / cm~3×10 -2 S / cm.

[0026] The Young's modulus of the phosphotungstic acid-based solid electrolyte material is 15 MPa to 130 MPa.

[0027] The relative density of the phosphotungstic acid-based solid electrolyte material is greater than or equal to 90% under cold pressing pressure of 50 MPa to 250 MPa.

[0028] In a second aspect, the present invention provides a method for preparing the phosphotungstic acid-based solid electrolyte material described in the first aspect, the method comprising:

[0029] Step S1: Dissolve phosphotungstic acid hydrate in deionized water, adjust the pH to 4.0–6.0, and stir the reaction at 60°C–90°C for 2–6 hours to obtain the vacant Keggin type [H3PW]. 11 O40] 2- Solution.

[0030] Step S2, add Al-containing solution to the solution obtained in step S1 3+ Soluble salts and Zr-containing 4+ The soluble salt was adjusted to pH 4.5–6.5, and the reaction was carried out at 60–90°C for 4–12 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water, and dried to obtain Al. 3+ and Zr 4+ Heterovalent co-skeletal substituted intermediates.

[0031] Step S3: Disperse the intermediate obtained in step S2 in a solvent, and add Li-containing... + The soluble salt is reacted at 40℃~80℃ for 2 hours to 8 hours. After the reaction is completed, it is filtered or centrifuged, then washed with deionized water and dried to obtain a lithium-ion partially substituted intermediate.

[0032] Step S4: Mix the intermediate obtained in step S3 with interstitial compound D, place it in a sealed container, and leave it at room temperature for 12 to 48 hours.

[0033] Step S5: The product obtained in step S4 is compounded with the organic plasticizer-lubricant bifunctional component L to obtain a composite material.

[0034] Step S6: Mix the composite material with oxide solid electrolyte powder to obtain phosphotungstic acid-based solid electrolyte material; the oxide mass fraction α is 0.05 to 0.5.

[0035] Preferably, the Al-containing 3+ The soluble salts include one or more of aluminum nitrate, aluminum chloride, aluminum acetate, or aluminum sulfate; the Zr-containing salts... 4+ Soluble salts include one or more of zirconium nitrate, zirconium oxychloride, zirconium sulfate, or zirconium acetate; the Al 3+ With the aforementioned [H3PW 11 O40] 2- The molar ratio is a:1, and the Zr 4+ With the aforementioned [H3PW 11 O40] 2- The molar ratio is b:1, where 0.05≤a≤1.5, 0.05≤b≤1.5, and 0.1≤a+b≤2.5.

[0036] Li + The soluble salts include one or more of lithium carbonate, lithium acetate, lithium nitrate, or lithium hydroxide; the Li + With the aforementioned [H3PW 11 O40] 2- The molar ratio is x:1, where 0.5≤x≤2.5.

[0037] The interstitial compound D comprises one or more of phosphorus pentoxide, silicon dioxide, or boron trioxide; the molar ratio of D to the lithium-ion partially substituted intermediate is z:1, wherein 0.01≤z≤0.3.

[0038] Preferably, in step S5, the composite process includes: dissolving the L in an anhydrous organic solvent to prepare an L solution with a mass fraction of 5% to 20%, dispersing the product obtained in S4 in the L solution, and stirring at room temperature to 60°C for 1 to 4 hours to allow the L to impregnate and adsorb onto the surface and grain boundaries of the product particles.

[0039] The mass ratio of L to the product obtained in step S4 is 5:100 to 30:100.

[0040] More preferably, step S5 further includes a ball milling-assisted compounding process, with a ball milling speed of 100 rpm to 400 rpm and a ball milling time of 0.5 hours to 2 hours.

[0041] Preferably, in step S6, the mixing method includes: liquid phase dispersion or ball milling-assisted compounding.

[0042] The liquid phase dispersion method includes: dispersing the oxide solid electrolyte powder in an anhydrous organic solvent, ultrasonically dispersing for 10 to 60 minutes, adding the composite material, stirring for 2 to 8 hours, and then vacuum drying to remove the solvent.

[0043] The ball milling-assisted compounding process includes: mixing the composite material with oxide powder, and then placing it in a planetary ball mill and ball milling it at a speed of 100 rpm to 400 rpm for 0.5 hours to 4 hours.

[0044] Thirdly, the present invention provides an all-solid-state lithium battery, the all-solid-state lithium battery comprising a positive electrode, a negative electrode and a solid electrolyte sheet, wherein the solid electrolyte sheet comprises the phosphotungstic acid-based solid electrolyte material described in the first aspect, or the phosphotungstic acid-based solid electrolyte material prepared by the preparation method described in the second aspect.

[0045] The present invention provides a phosphotungstic acid-based solid electrolyte material, its preparation method and application, which has the following technical effects.

[0046] (1) The preparation method of the phosphotungstic acid-based solid electrolyte material provided by the present invention firstly dissolves phosphotungstic acid hydrate in deionized water, adjusts the pH value to weakly acidic, and stirs the reaction under heating conditions to obtain a vacant Keggin-type precursor solution; then, Al-containing... 3+ Soluble salts and Zr-containing 4+ The soluble salts, controlling the amounts of Al and Zr added, adjusting the pH value, and continuing the reaction under heating conditions with stirring, allow Al to... 3+ and Zr 4+ By jointly embedding the missing positions of the Keggin skeleton, the W in the skeleton can be achieved. 6+ Heterovalent co-substitution, in which Al 3+ and Zr 4+ The synergistic introduction of [the substance] generates a triple effect: charge compensation creates lithium vacancies, large and small ions synergistically alter the lattice, and Zr-O strong bonds stabilize the framework; subsequently, the obtained intermediate is dispersed in deionized water or anhydrous ethanol, and Li-containing [substances] are added. + The soluble salt of Li was reacted under heating and stirring to produce Li + Partially replaces H +The interstitial sites or surface sites of the Keggin framework are entered; the resulting product is then mixed with interstitial doping elements or compounds, ground uniformly, and placed in a sealed container to allow the interstitial components to fully penetrate the interlayer to expand the interlayer spacing and control the water content; next, the resulting product is composited with an organic plasticizing and lubricating bifunctional component, allowing the organic component to wet and adsorb onto the surface of the product particles and grain boundaries to form an amorphous continuous phase; then, the resulting composite material is mixed with oxide solid electrolyte powder to uniformly disperse the oxide in the composite material; finally, the composite powder is placed in a mold for cold pressing, and after demolding, a solid electrolyte sheet is obtained. The entire preparation process is completed in a dry atmosphere.

[0047] The preparation method provided by this invention completes Al production under mild conditions via a solution method. 3+ and Zr 4+ W in the Keggin skeleton 6+ The heterovalent co-substitution can be carried out in an aqueous system at 60℃ to 90℃, avoiding the hundreds of degrees required for traditional high-temperature solid-phase reactions. This effectively prevents problems such as Keggin framework collapse, phase separation and element volatilization that may be caused by high-temperature treatment, and ensures the integrity and consistency of the product structure.

[0048] The preparation method provided by this invention achieves Al through the design of a vacancy-deficient Keggin precursor. 3+ and Zr 4+ Precise embedding within the skeleton, with pre-reserved gaps in the precursor for Al 3+ and Zr 4+ It provides selective site guidance, enabling precise control of heterovalent co-substitution at the molecular level, avoiding the formation of impurity phases and ensuring the phase purity of the product.

[0049] The preparation method provided by this invention adopts a stepwise approach to sequentially complete the skeleton heterovalent co-substitution, lithium ion exchange, interstitial doping, organic composite and oxide composite. Each step does not interfere with each other and has a synergistic effect, so that the charge compensation effect of Al and Zr heterovalent co-substitution, the interlayer widening effect of interstitial compound interstitial doping, the flexible buffering effect of PEG and the interfacial conduction effect of oxide particles can be fully exerted and ultimately work synergistically to improve the overall performance of the material.

[0050] The preparation method provided by this invention has a wide process window and strong versatility, applicable to various oxide solid electrolyte systems such as LLZO, TA-LLZTO, and LATP. The reaction temperature, time, pH value, and proportions of each step have considerable adjustability, facilitating process optimization and scale-up production according to specific needs. The entire preparation process involves only conventional solution stirring, mixing, drying, and cold pressing operations, requiring no special equipment and suitable for large-scale production.

[0051] (2) The phosphotungstic acid-based solid electrolyte material prepared by the preparation method provided by the present invention maintains the integrity of the Keggin framework structure, has no impurity phase generation, and has a wide electrochemical stability window and high lithium ion transference number. Its comprehensive performance indicators surpass those of existing phosphotungstic acid-based solid electrolyte materials.

[0052] In terms of ion conduction, Al 3+ With Zr 4+ Heterovalent co-substitution creates a large number of lithium vacancies through charge compensation effects, increasing carrier concentration, while Al 3+ Small radius shrinkage effect and Zr 4+ The large radius expansion effect synergistically generates abundant lattice distortion, providing diverse low-barrier jumping paths for lithium ions. The stabilizing effect of the Zr-O strong bond on the Keggin framework ensures the long-term structural integrity of the ion channels. The synergy of these three factors significantly improves the intrinsic ionic conductivity compared to the unmodified material. On this basis, interstitial doping of interstitial compounds expands the interlayer spacing, further reducing the spatial resistance of ion migration. The coordination exchange between the ether oxygen functional groups provided by the PEG amorphous continuous phase and lithium ions accelerates ion transport at the interface. The long-range interfacial channels constructed by oxide nanoparticles compensate for the path limitations of single-phase conduction.

[0053] In terms of mechanical properties, the PEG amorphous continuous phase coats the surface and grain boundaries of Keggin nanocrystalline particles, effectively isolating direct contact between rigid particles and reducing the Young's modulus of the material to a level far lower than that of traditional oxide electrolytes, thus completely breaking the inherent technical prejudice that high ionic conductivity must be accompanied by high material rigidity.

[0054] In terms of molding performance, the introduction of organic lubricating components reduces the coefficient of friction between particles, enabling the material to achieve high relative density at lower pressures. This avoids residual stress and microcracks associated with high-pressure molding and prevents excessive compression from blocking ion channels. Regarding environmental stability, interstitial doping significantly improves the material's moisture resistance through its moderate binding effect on water molecules.

[0055] (3) The phosphotungstic acid-based solid electrolyte material prepared by this invention is applied to all-solid-state lithium batteries, and its technical effect is reflected in the overall improvement of the battery performance.

[0056] In terms of interface properties, the material’s low Young’s modulus allows the electrolyte sheets to undergo moderate deformation under battery assembly pressure, forming a tight solid-solid contact with the positive and negative electrode active material particles, effectively increasing the actual contact area and significantly reducing the interfacial contact resistance, which is much lower than that of pure oxide electrolytes.

[0057] In terms of ion conduction, the large number of lithium vacancies created by Al / Zr heterovalent co-substitution inside the material and the construction of multi-level ion channels give the electrolyte bulk phase high ion conductivity, ensuring high-speed transport of lithium ions inside the electrolyte layer. The tight interfacial contact and high bulk conductivity work together to enable all-solid-state lithium batteries to output high capacity and power density at room temperature.

[0058] In terms of cycle stability, the stabilizing effect of Zr-O strong bonds on the Keggin framework and the buffering absorption of volume changes by the PEG amorphous continuous phase during cycling effectively suppress the structural degradation and interface deterioration of the electrolyte during repeated charge and discharge. At the same time, the wide electrochemical stability window ensures that the electrolyte does not undergo oxidative decomposition in the high-voltage cathode material system. The synergy of these factors enables the battery to exhibit excellent cycle life.

[0059] In terms of safety performance, the all-solid-state electrolyte design completely eliminates liquid organic electrolytes, fundamentally avoiding safety hazards such as leakage, combustion and explosion. The inherent low Young's modulus of the material also gives the electrolyte layer the ability to resist mechanical bending and vibration, further improving the reliability and durability of the battery in complex application scenarios. Attached Figure Description

[0060] Figure 1 A flowchart illustrating the preparation method of phosphotungstic acid-based solid electrolyte material provided in this embodiment of the invention. Detailed Implementation

[0061] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0062] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0063] To facilitate a better understanding of the present invention, some technical terms will be explained below.

[0064] The technical term "Keggin-type structure" refers to a cage-like molecular structure with full tetrahedral symmetry, consisting of a central heteroatom and four oxygen atoms forming a tetrahedron, surrounded by 12 transition metal atoms each coordinated with an oxygen atom to form an octahedron, and the 12 octahedra tightly enclosing the central tetrahedron through shared edges and corners. Its general molecular formula is [XM]. 12 O40] n- , where X is a heteroatom and M is a transition metal atom.

[0065] The technical term "vacant Keggin type" refers to a polyoxometalate structure with empty coordination sites formed by removing one or more MO6 octahedra from the complete Keggin structure. The oxygen atoms exposed on its surface become active coordination sites that can selectively coordinate and intercalate with metal ions.

[0066] The technical term "heterovalent co-substitution" refers to a modification strategy that simultaneously introduces two metal ions with different valence states than the matrix element into the same Keggin framework to replace framework sites. After substitution, lithium vacancies are generated or additional lithium ions are introduced to maintain the charge balance system, thereby regulating ion transport performance.

[0067] The technical term "core-shell structure" refers to a three-layer structure of a solid electrolyte material, consisting of a core, an intermediate transition layer, and a functional outer shell, arranged sequentially from the inside out. The core is Al. 3+ and Zr 4+ The heterovalent co-doped Keggin-type phosphotungstic acid anionic nanocrystals have an intermediate transition layer consisting of an Al / Zr heterovalent co-doped charge reconstruction region and a compositional gradient interface, and an outer functional layer consisting of an organic-inorganic hybrid layer with an organic plasticizer-lubricant bifunctional component and an oxide solid electrolyte interpenetrating.

[0068] The technical term "Keggin terminal oxygen forming MO-Al / Zr / W bridging bond" refers to the chemical bridging structure formed between the oxygen atoms of the metal ion M on the surface of the oxide solid electrolyte and the terminal oxygen atoms of Al, Zr, and W in the Keggin framework. Specifically, the M ion on the oxide solid electrolyte surface establishes covalent or strong coordination bonds with the exposed terminal oxygen atoms of the Keggin framework through its coordinated oxygen atoms. This bridging structure connects the Keggin unit to the oxide solid electrolyte particle. Al / Zr / W represent different Keggin framework sites: unsubstituted W site terminal oxygen can form a WOM bond, Al substituted site terminal oxygen can form an Al-OM bond, and Zr substituted site terminal oxygen can form a Zr-OM bond.

[0069] The technical term "charge compensation effect" refers to the mechanism by which defects are spontaneously generated or additional ions are introduced into the system to maintain the overall charge balance of the crystal lattice when low-valence ions replace high-valence ions. When trivalent aluminum ions and tetravalent zirconium ions replace hexavalent tungsten ions, the negative charge of the Keggin anion increases, which generates a large number of lithium vacancies or introduces additional lithium ions into interstitial sites to maintain the charge balance of the system.

[0070] The technical term "lithium vacancy" refers to the vacancy defect generated at the lithium ion site due to the charge compensation requirement caused by heterovalent substitution. This vacancy defect acts as a stepping stone for lithium ion hopping, reducing the ion migration activation energy, increasing the concentration of hopping sites for charge carriers, and thus improving ionic conductivity.

[0071] The technical term "large and small ion synergistic lattice distortion" refers to Al 3+ Small radius shrinkage effect and Zr 4+ The large radius expansion effect generates differentiated occupation and complementary structural regulation in the Keggin skeleton, Al 3+ The ionic radius is 0.535 Å, which is less than W. 6+ The 0.60 Å value causes local lattice contraction, creating active sites in Zr. 4+ The ionic radius is 0.72 Å, which is greater than W. 6+ The 0.60 Å ion causes local lattice expansion, widening the ion channels. The two differentiating positions occupy different sites in the Keggin framework, creating a richer and more diverse range of lithium-ion hopping pathways than a single substitution system.

[0072] The technical term "organic plasticizer-lubricant dual-function component" refers to an organic component that has the dual functions of plasticizing to reduce Young's modulus and lubricating to improve cold pressing formability. It forms an amorphous continuous phase that coats the surface and grain boundaries of Keggin nanocrystalline particles to isolate rigid particles from direct contact and reduce material rigidity. At the same time, it reduces the coefficient of friction between particles during cold pressing to improve densification effect.

[0073] The technical term "interstitial doping" refers to a doping method in which doped atoms or compounds are embedded in the interstitial positions of the matrix lattice rather than replacing the original atomic sites. P2O5 molecules enter the interlayer gaps between Keggin units and exert a layer expansion effect, increasing the Keggin unit spacing and providing more free space for lithium ion migration to reduce steric hindrance.

[0074] The technical term "cold pressing" refers to a process in which powder materials are densified and formed by mechanical pressure at room temperature without the application of an external heat source. The composite powder is placed in a mold and pressed under pressure of 50MPa to 250MPa and held under pressure for 1 to 10 minutes before being demolded to obtain a solid electrolyte sheet.

[0075] Based on an understanding of the above terminology, the technical solution of the present invention will be further described in detail below.

[0076] The present invention provides a phosphotungstic acid-based solid electrolyte material, comprising: a core, an intermediate transition layer, and a shell functional layer.

[0077] Among them, the kernel is Al 3+ and Zr 4+ Heterovalent co-doped Keggin-type phosphotungstic acid anion nanocrystals; these nanocrystals are the core carriers for the material to perform ion conduction functions.

[0078] An intermediate transition layer covers the surface of the core and contains Al 3+ and Zr 4+The charge reconstruction region and composition gradient interface induced by heterovalent co-doping; this intermediate transition layer plays a key role in connecting the core and shell, eliminating lattice mismatch and space charge layer effects.

[0079] The outer shell functional layer covers the surface of the intermediate transition layer and includes an organic-inorganic hybrid layer in which organic plasticizer-lubricant dual-function components and oxide solid electrolyte interpenetrate; the outer shell functional layer covers multiple functions including mechanical buffering, molding lubrication and interfacial ion transport.

[0080] The structure consisting of the core, intermediate transition layer, and outer shell functional layer, through the synergistic effect of chemical bonding and physical coating, constitutes a composite material system with multi-level ion channels and gradient mechanical response characteristics.

[0081] Specifically, the general chemical formula of the phosphotungstic acid-based solid electrolyte material provided in this embodiment of the invention is: (1-α)[Li x H (3-x) Al a Zr b PW 12-(a+b) O 40 ·mH2O·nL·zD]+α[Oxide]; Among them, Li x H (3-x) Al a Zr b PW 12-(a+b) O 40 ·mH2O is Al 3+ and Zr 4+ The general chemical formula for heterovalent co-doped Keggin-type phosphotungstic acid anionic nanocrystals is 0.5≤x≤4.0, 0.05≤a≤1.5, 0.05≤b≤1.5, 0.1≤a+b≤2.5, and 0≤m≤8.

[0082] When the x value is too low, Li can migrate freely in the material. + Insufficient quantity means that even with abundant lithium vacancies and unobstructed transport channels, high ionic conductivity cannot be achieved due to limited carrier supply. Simultaneously, excessive H+... + The presence of [a certain substance] introduces a competition mechanism for proton conduction, interfering with the directional migration of lithium ions and reducing the electrochemical stability window. Furthermore, when the value of x is too high, excess Li [a certain substance]... + It will excessively occupy the interstitial and surface sites of the Keggin framework, thereby blocking the original Li + The vacancy channels in the jump design reduce the relative concentration of lithium vacancies. However, the introduction of excessive lithium salt may introduce impurity phases, affecting the interfacial purity and long-term stability of the material.

[0083] When the value of a is less than 0.05, Al³ +When the amount of Al³⁺ introduced is too small, the charge compensation effect is not significant, the resulting lithium vacancy concentration is insufficient to substantially affect the ionic conductivity, and the degree of lattice distortion is also very limited, failing to effectively enrich the ion jumping paths. Therefore, the material performance shows no significant improvement compared to the unmodified system. However, when the a value is higher than 1.5, excess Al³⁺… + The introduction of Al³⁺ can lead to severe framework charge imbalance. The Keggin structure may experience irreversible lattice distortion or even structural collapse due to over-substitution. Furthermore, excessive lithium vacancies may form vacancy clusters or orderly vacancy arrangements that hinder rather than promote ion migration. + It may also segregate to grain boundaries to form amorphous phase impurities, reducing the crystallinity and electrochemical stability of the material.

[0084] When the b value is less than 0.05, Zr 4+ Neither the expansion effect nor the skeletal stabilization effect can be fully manifested, and the expansion of the channel size is insufficient to significantly reduce Li + The migration resistance is high, and the skeleton is prone to structural degradation during subsequent processing and use. When the b value is higher than 1.5, excessive Zr... 4+ The introduction of Zr can cause excessive expansion of the framework, and the excessively large local channel size can actually damage the structural integrity of the Keggin anion. Simultaneously, excessive Zr... 4+ It may segregate in the form of zirconium oxide, becoming a grain boundary impurity phase, increasing interfacial impedance and reducing the ion selectivity of the material.

[0085] M represents the amount of water of crystallization. When the value of m is too low, the material is too dry, there is a lack of water molecule bridging between Keggin units, the continuity of ion transport deteriorates, and the material's flexibility decreases. When the value of m is too high, excessive water molecules will occupy the pore space and block the ion channels. At the same time, a large number of protons and hydroxide ions will be introduced, which will aggravate the interference of proton conduction on lithium ion conduction. It may also lead to excessive hygroscopicity of the material, which will affect the environmental adaptability during battery assembly.

[0086] L represents the organic plasticizer-lubricant bifunctional component, and n represents the mass ratio of the organic plasticizer-lubricant bifunctional component to Keggin-type phosphotungstic acid anionic nanocrystals, where 0.05 ≤ n ≤ 0.3. When n is less than 0.05, the organic component content is too low to form a continuous and complete coating layer, resulting in numerous direct contact points between rigid particles, a persistently high Young's modulus, and insignificant lubrication effect, requiring high pressure during cold pressing. When n is greater than 0.3, while excessive organic component further reduces the modulus, it forms an excessively thick organic layer between particles. Since the intrinsic ionic conductivity of the organic component is much lower than that of the inorganic phase, the excessively thick organic layer significantly increases the interfacial resistance to ion transport, leading to a decrease in overall conductivity. Furthermore, excessive organic matter may undergo electrochemical side reactions during long-term battery operation, reducing cycle stability.

[0087] Organic plasticizer-lubricant bifunctional components include one or more of polyethylene glycol (PEG), polyethylene oxide (PEO), or polypropylene oxide (PPO).

[0088] D represents the interstitial compound, and z represents the molar ratio of D to Keggin-type phosphotungstic acid anionic nanocrystals, where 0.01 ≤ z ≤ 0.3. The interstitial compound includes one or more of P2O5, SiO2, or B2O3.

[0089] Oxide represents oxide solid electrolyte, with a value of 0.05 ≤ α ≤ 0.5. When α is below 0.05, the oxide content is too low to form an effective long-range continuous conductive network, resulting in limited improvement in conductivity and failing to fully utilize the interfacial conduction advantages of the composite material. When α is above 0.5, excessive oxide particles lead to a relatively insufficient proportion of flexible organic components in the composite material, increasing the overall rigidity of the material and significantly raising the Young's modulus, deviating from the low modulus range of 15 MPa to 130 MPa. Furthermore, the introduction of excessive oxide solid electrolyte particles increases the number of interparticle interfaces, potentially introducing additional interfacial impedance rather than reducing it. Oxide solid electrolytes include one or more of LATP, LLZO, or TA-LLZTO. The chemical formula of LLZO is Li7La3Zr2O. 12 The chemical formula of TA-LLZTO is Li. 6.4 La3Zr 1.4 Ta 0.8 O 12 The chemical formula of NASICON-type LATP is Li. 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0090] The particle size Dv50 of Keggin-type phosphotungstic acid anionic nanocrystals ranges from 5 nm to 20 nm, and can be any value within this range, such as 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, etc., but is not limited to the listed values; other unlisted values ​​within this range also apply. When the particle size is greater than 20 nm, the particle size is too large, the specific surface area is significantly reduced, the reaction efficiency of aluminum ion and zirconium ion substitution decreases, and the voids between large particles are difficult to completely eliminate under cold pressing, resulting in a decrease in the relative density after molding, and it is also difficult to achieve uniform coverage of the particle surface coating.

[0091] The room temperature ionic conductivity of the phosphotungstic acid-based solid electrolyte material is 1×10⁻⁶. -2 S / cm~3×10 -2 S / cm.

[0092] The Young's modulus of phosphotungstic acid-based solid electrolyte materials ranges from 15 MPa to 130 MPa, and can be any value within this range, such as 15 MPa, 20 MPa, 30 MPa, 40 MPa, 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa, 100 MPa, 110 MPa, 120 MPa, 130 MPa, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0093] The relative density of phosphotungstic acid-based solid electrolyte materials is greater than or equal to 90% under cold pressing pressure of 50MPa to 250MPa.

[0094] This invention provides a method for preparing the above-mentioned phosphotungstic acid-based solid electrolyte material, such as... Figure 1 As shown, the specific steps include:

[0095] Step S1: Dissolve phosphotungstic acid hydrate in deionized water, adjust the pH to 4.0–6.0, and stir the reaction at 60°C–90°C for 2–6 hours to obtain the vacant Keggin type [H3PW]. 11 O40] 2- Solution.

[0096] Step S2, add Al-containing solution to the solution obtained in step S1 3+ Soluble salts and Zr-containing 4+ The soluble salt was adjusted to pH 4.5–6.5, and the reaction was carried out at 60–90°C for 4–12 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water, and dried to obtain Al. 3+ and Zr 4+ Heterovalent co-skeletal substituted intermediates.

[0097] Among them, containing Al 3+ Soluble salts include one or more of aluminum nitrate, aluminum chloride, aluminum acetate, or aluminum sulfate.

[0098] Contains Zr 4+ Soluble salts include one or more of zirconium nitrate, zirconium oxychloride, zirconium sulfate, or zirconium acetate.

[0099] Al 3+ With [H3PW] 11 O40] 2- The molar ratio of Zr is a:1. 4+ With [H3PW] 11 O40] 2- The molar ratio is b:1, where 0.05≤a≤1.5, 0.05≤b≤1.5, and 0.1≤a+b≤2.5.

[0100] Step S3: Disperse the intermediate obtained in step S2 in a solvent, and add Li-containing... + The soluble salt is reacted at 40℃~80℃ for 2 hours to 8 hours. After the reaction is completed, it is filtered or centrifuged, then washed with deionized water and dried to obtain a lithium-ion partially substituted intermediate.

[0101] Among them, Li + Soluble salts include one or more of lithium carbonate, lithium acetate, lithium nitrate, or lithium hydroxide; Li + With [H3PW] 11 O40] 2- The molar ratio is x:1, where 0.5≤x≤2.5.

[0102] Step S4: Mix the intermediate obtained in step S3 with interstitial compound D, place it in a sealed container, and leave it at room temperature for 12 to 48 hours.

[0103] The interstitial compound D includes one or more of phosphorus pentoxide, silicon dioxide, or boron trioxide; the molar ratio of D to the lithium-ion partially substituted intermediate is z:1, where 0.01≤z≤0.3.

[0104] Step S5: The product obtained in step S4 is compounded with the organic plasticizer-lubricant bifunctional component L to obtain a composite material.

[0105] This step also includes a ball milling-assisted compounding process, with a ball milling speed of 100 rpm to 400 rpm and a ball milling time of 0.5 hours to 2 hours.

[0106] The composite process specifically includes: dissolving L in an anhydrous organic solvent to prepare an L solution with a mass fraction of 5% to 20%; dispersing the product obtained in step S4 in the L solution; and stirring at room temperature to 60°C for 1 to 4 hours to allow L to wet and adsorb onto the surface and grain boundaries of the product particles. The mass ratio of L to the product obtained in step S4 is 5:100 to 30:100.

[0107] Step S6: Mix the composite material with oxide solid electrolyte powder to obtain phosphotungstic acid-based solid electrolyte material.

[0108] The mass fraction α of the oxide is 0.05 to 0.5.

[0109] Mixing methods include liquid phase dispersion or ball milling-assisted compounding.

[0110] Specifically, the liquid phase dispersion method includes: dispersing the oxide solid electrolyte powder in an anhydrous organic solvent, ultrasonically dispersing for 10 to 60 minutes, adding the composite material, stirring for 2 to 8 hours, and then vacuum drying to remove the solvent.

[0111] Ball milling-assisted compounding includes mixing the composite material with oxide powder and then placing it in a planetary ball mill and ball milling it at a speed of 100 rpm to 400 rpm for 0.5 hours to 4 hours.

[0112] The phosphotungstic acid-based solid electrolyte material provided in this embodiment of the invention can be cold-pressed under a pressure of 50MPa to 250MPa and held under pressure for 1 minute to 10 minutes to obtain a solid electrolyte sheet.

[0113] This invention achieves densification by replacing high-temperature sintering with cold pressing. The forming pressure is only 50MPa to 250MPa, which is much lower than the high-temperature sintering process of hundreds of degrees required by traditional ceramic electrolytes. This fundamentally simplifies the process, reduces energy consumption and equipment requirements, and avoids the problems of abnormal grain growth and thermal stress cracking caused by high-temperature sintering.

[0114] The solid electrolyte sheet provided in this embodiment of the invention can be assembled with the positive electrode and the negative electrode to form an all-solid-state lithium battery.

[0115] To better understand the technical solution provided by the present invention, the preparation method and characteristics of the phosphotungstic acid-based solid electrolyte material of the present invention are described below with several specific examples.

[0116] Example 1 This embodiment provides a method for preparing a phosphotungstic acid-based solid electrolyte material, which specifically includes the following steps.

[0117] (1) Take 5.0g of phosphotungstic acid hydrate H3PW 12 O 40 • 29H2O was dissolved in 100 mL of deionized water to prepare a 10% (w / w) solution. The pH was adjusted to 5.0 with dilute ammonia. The mixture was stirred at 80 °C for 4 hours to obtain the vacant Keggin-type [H3PW] 11 O 40 ] 2- Solution.

[0118] (2) Under stirring conditions, slowly add 0.196 g of aluminum nitrate nonahydrate and 0.168 g of zirconium oxychloride octahydrate to the solution obtained in step (1) in sequence, wherein Al reacts with [H3PW 11 O40] 2- The molar ratio a is 0.3:1, Zr and [H3PW 11 O40] 2-The molar ratio b was 0.3:1, and the total substitution amount a+b was 0.6. The pH was adjusted to 5.5 with dilute ammonia, and the reaction was continued to be stirred at 80°C for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times with deionized water, and dried under vacuum at 70°C to obtain Al. 3+ and Zr 4+ Heterovalent co-skeletal substituent intermediate H 2.5 Al 0.3 Zr 0.3 PW 11.4 O 40 ·2H2O.

[0119] (3) The intermediate obtained in step (2) was dispersed in 50 mL of anhydrous ethanol, and 0.096 g of lithium carbonate was slowly added under stirring at 50 °C. The reaction was carried out for 4 hours. After the reaction was completed, the mixture was filtered, washed three times with deionized water, and dried under vacuum at 60 °C to obtain the lithium-ion partially substituted intermediate. The molar ratio x of Li to skeletal substituted phosphotungstic acid was 1.5:1.

[0120] (4) Mix all the intermediates obtained in step (3) with 0.0173g of interstitial compound D, wherein interstitial compound D is P2O5, and place in a sealed container and leave at room temperature for 24 hours; wherein the molar ratio of P2O5 to intermediate is 0.07:1.

[0121] (5) The organic plasticizer-lubricant bifunctional component L polyethylene glycol (PEG) 400 The product obtained in step (4) was dissolved in anhydrous ethanol to prepare a 10% (w / w) PEG solution. The product obtained in step (4) was dispersed in the PEG solution and stirred at 40°C for 2 hours to allow the PEG to fully wet and adsorb onto the surface and grain boundaries of the product particles. Subsequently, the ethanol was removed by vacuum drying at 60°C to obtain the composite material. The product obtained in step (4) and the PEG 400 The mass ratio is 100:15. This step also includes a ball milling auxiliary compounding process, where the balls are milled at 200 rpm for 1 hour.

[0122] (6) The nanoscale oxide solid electrolyte Li 6.4 La3Zr 1.4 Ta 0.8 O 12 The powder of (TA-LLZTO) was pre-dried under vacuum at 80°C for 12 hours; 0.15g of Ta-LLZTO was dispersed in anhydrous ethanol and ultrasonically dispersed for 30 minutes. 0.85g of the composite material obtained in step (5) was added and stirred for 4 hours to mix. Then, the solvent was removed by vacuum drying at 60°C to obtain phosphotungstic acid-based solid electrolyte material.

[0123] The chemical formula of the phosphotungstic acid-based solid electrolyte material prepared in this embodiment is: 0.85[Li 1.5 H 1.5 Al 0.3 Zr 0.3 PW 11.4 O 40 ·2H2O·0.15PEG·0.07P2O5]+0.15[TA-LLZTO].

[0124] (7) The phosphotungstic acid-based solid electrolyte material prepared in this embodiment is placed in a stainless steel mold with a diameter of 10 mm, and cold-pressed under a pressure of 200 MPa for 5 minutes. After demolding, the solid electrolyte sheet is obtained.

[0125] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the phosphotungstic acid-based solid electrolyte material prepared in this embodiment were tested. The specific test methods are as follows, and the test data are detailed in Table 1.

[0126] The Young's modulus test method is as follows: The Young's modulus of the solid electrolyte sheet obtained in step (7) is tested using a nanoindenter at room temperature (25℃). Before testing, the surface of the solid electrolyte sheet is polished to ensure that its surface roughness Ra ≤ 50 nm. A Berkovich diamond indenter is used, and loading is performed in continuous stiffness measurement mode. The maximum indentation depth is set to 500 nm, the loading rate is 0.05 / s, and the thermal drift is controlled to be less than 0.05 nm / s. During the test, the loading-unloading curve is recorded, and the unloading curve is analyzed using the Oliver-Pharr method to calculate the contact stiffness and obtain the Young's modulus value of the material. At least 10 different locations are selected for testing for each sample, and the average value is taken as the final result. The Poisson's ratio is taken as 0.3 for calculation.

[0127] The relative density test method is as follows: the relative density of the solid electrolyte sheet is tested using Archimedes' displacement method. The cold-pressed electrolyte sheet is dried at 105℃ to constant weight, and the dry weight (m1) of the sample in air is measured. Using anhydrous ethanol as the impregnation medium, the sample is placed in anhydrous ethanol and vacuum-treated for 30 minutes to remove air bubbles from the pores on the sample surface. After the sample is completely impregnated, the suspended weight (m2) of the sample in the medium is measured. The sample is removed, and the surface-adhered medium is gently absorbed with filter paper. The weight (m3) of the saturated sample in air is then measured. The sample volume (V) is calculated using the formula V = (m3 - m2) / ρethanol, where ρethanol is taken as 0.789 g / cm³. 3 The sample density ρ = m1 / V. The relative density is the ratio of the sample density to the theoretical density multiplied by 100%. The theoretical density is calculated from the densities of each constituent phase according to the mixing rule. Each sample is measured three times, and the average value is taken as the final result.

[0128] The method for testing room temperature ionic conductivity is as follows: The ionic conductivity of the solid electrolyte sheet is tested using AC impedance spectroscopy. The solid electrolyte sheet is surface polished, and silver paste is symmetrically coated on both sides of the sheet as blocking electrodes. It is then vacuum dried at 120°C for 2 hours. The assembled sample is placed in a constant temperature chamber, and the test temperature is controlled at 25°C. AC impedance testing is performed using an electrochemical workstation with a frequency scan range of 1Hz to 1MHz and an applied AC amplitude of 10mV. Before testing, the sample is kept at the test temperature for 30 minutes to achieve thermal equilibrium. The AC impedance spectrum of the electrolyte is measured and recorded. The Nyquist plot is fitted using an equivalent circuit model to obtain the bulk resistance R of the electrolyte. The ionic conductivity σ is calculated using the formula σ = L / (R × S), where L is the thickness of the electrolyte sheet and S is the electrode area. In this embodiment, the electrode area is approximately 0.785 cm². 2 Each sample was tested three times, and the average value was taken as the final result. The thickness L was measured at five evenly selected locations on the sheet using a micrometer, and the average value was taken.

[0129] The electrochemical window testing method was as follows: the electrochemical stability window of the phosphotungstic acid-based solid electrolyte material in this embodiment was tested using linear scanning voltammetry. After polishing the surface of the solid electrolyte sheet, a two-electrode system was assembled using stainless steel foil as the working electrode and lithium metal sheet as the counter and reference electrodes. The test was conducted at room temperature, using an electrochemical workstation to perform a forward potential scan from the open circuit potential to higher potentials at a scan rate of 1 mV / s. The upper limit of the scan was set to 6.0 V vs. Li. + / Li. During the test, the curve of current changing with potential was recorded. When the current density showed a significant and sustained sudden increase, the potential corresponding to this sudden increase point was the upper limit of the electrochemical stability window of the material. At least three test cells were assembled for each sample for parallel testing.

[0130] The lithium-ion transference number (LTL) test method was employed: the Bruce-Vincent-Evans method was used to test the LTL of the solid electrolyte material. After polishing the surface of the solid electrolyte sheet, lithium metal electrodes were symmetrically assembled on both sides to form a Li|electrolyte|Li symmetrical blocking battery. First, the battery was subjected to an AC impedance test at an open-circuit potential, with a frequency range of 1 Hz to 1 MHz and an amplitude of 10 mV, to obtain the initial interfacial impedance R0 of the electrolyte before the test. Then, a constant potential step signal of 10 mV was applied to the battery, and the change curve of the polarization current over time was recorded until the current reached a steady state, at which point the steady-state current I was recorded. ss Once the polarization current reaches a steady state, the battery is subjected to an AC impedance test again to obtain the steady-state interface impedance R. ss Lithium-ion transport number t_Li + According to the formula t_Li + =I ss(ΔV-I0R0) / [I0(ΔV-I ss R ss The calculation is performed, where ΔV is the applied constant potential step value and I0 is the initial current peak value. Tests were conducted at room temperature, with each sample assembled with at least three symmetrical cells for parallel testing.

[0131] The solid electrolyte sheets prepared in this embodiment are used to assemble CR2032 coin cells. The specific process is as follows: The preparation of the electrode sheet is as follows: the solid electrolyte sheet after cold pressing in step (7) is used as the solid electrolyte layer, and assembled with the positive electrode sheet and the negative electrode sheet to form an all-solid-state lithium battery. The preparation method of the positive electrode sheet is as follows: the lithium iron phosphate positive electrode active material, the conductive additive Super P and the binder polyvinylidene fluoride are weighed in a mass ratio of 8:1:1, an appropriate amount of N-methylpyrrolidone solvent is added, and the mixture is stirred evenly at room temperature to prepare a positive electrode slurry; the slurry is evenly coated on the aluminum foil current collector, dried in a forced-air drying oven at 80°C, then cut into circular electrode sheets with a diameter of 12mm, and then placed in a vacuum drying oven at 100°C for 12 hours. The negative electrode uses a lithium metal sheet.

[0132] The assembly of the all-solid-state battery was carried out in a glove box filled with high-purity argon gas. The batteries were stacked in the following order: positive electrode shell - positive electrode plate - solid electrolyte sheet - negative electrode plate - stainless steel gasket - spring sheet - negative electrode shell. The batteries were encapsulated using a CR2032 button cell casing at a pressure of 50 MPa.

[0133] The assembled CR2032 coin cell was tested using a Blue Battery testing system, which performed constant current charge-discharge tests on the all-solid-state battery. The test temperature was room temperature (25℃), and the charge-discharge voltage range was 2.5V~4.2V (vs. Li). + The battery (Li) was charged and discharged at rates of 0.1C, 0.2C, 0.5C, and 1C. The initial discharge specific capacity, initial coulombic efficiency, discharge specific capacity at different rates, and capacity retention after 100 cycles were recorded. Detailed test data are shown in Table 2.

[0134] Example 2 This embodiment provides a preparation process for a phosphotungstic acid-based solid electrolyte material, which specifically includes the following steps.

[0135] (1) Preparation of vacancy-deficient Keggin type [H3PW] 11 O40] 2- The solution process is the same as step (1) in Example 1.

[0136] (2) Under stirring conditions, slowly add 0.391 g of aluminum nitrate nonahydrate and 0.084 g of zirconium oxychloride octahydrate to the solution obtained in step (1) in sequence, wherein Al reacts with [H3PW 11 O40] 2- The molar ratio a is 0.6:1, Zr and [H3PW 11 O40] 2- The molar ratio b was 0.15:1, and the total substitution amount a+b was 0.75. The pH was adjusted to 5.5 with dilute ammonia, and the reaction was continued to be stirred at 80°C for 8 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times with deionized water, and dried under vacuum at 70°C to obtain Al. 3+ and Zr 4+ Heterovalent co-skeletal substituent intermediate H 2.25 Al 0.6 Zr 0.15 PW 11.25 O 40 ·2H2O.

[0137] (3) The intermediate obtained in step (2) was dispersed in 50 mL of anhydrous ethanol, and 0.116 g of lithium carbonate was slowly added under stirring at 50 °C. The reaction was carried out for 4 hours. After the reaction was completed, the mixture was filtered, washed three times with deionized water, and dried under vacuum at 60 °C to obtain the lithium-ion partially substituted intermediate. The molar ratio x of Li to skeletal substituted phosphotungstic acid was 1.8:1.

[0138] (4) Mix all the intermediates obtained in step (3) with 0.0123g of interstitial compound D (P2O5), place them in a sealed container, and leave them at room temperature for 24 hours; wherein the molar ratio of P2O5 to the intermediate is 0.05:1.

[0139] (5) The organic plasticizer-lubricant bifunctional component L polyethylene glycol (PEG) 400 The product obtained in step (4) was dissolved in anhydrous ethanol to prepare a 10% (w / w) PEG solution. The product obtained in step (4) was dispersed in the PEG solution and stirred at 40°C for 2 hours to allow the PEG to fully wet and adsorb onto the surface and grain boundaries of the product particles. Subsequently, the ethanol was removed by vacuum drying at 60°C to obtain the composite material. The product obtained in step S4 and the PEG 400 The mass ratio is 100:20. This step also includes a ball milling auxiliary compounding process, where the balls are milled at 300 rpm for 1.5 hours.

[0140] (6) The powder of nano-sized oxide solid electrolyte LATP was vacuum dried at 80°C for 12 hours; 0.20g of LATP was dispersed in anhydrous ethanol and ultrasonically dispersed for 30 minutes. 0.80g of the composite material obtained in step (5) was added and stirred for 4 hours to mix. Then, the solvent was removed by vacuum drying at 60°C to obtain phosphotungstic acid-based solid electrolyte material.

[0141] The chemical formula of the phosphotungstic acid-based solid electrolyte material prepared in this embodiment is: 0.80[Li 1.8 H 1.5 Al 0.6 Zr 0.15 PW 11.25 O 40 ·2H2O·0.20PEG·0.07 P2O5]+0.20[LATP].

[0142] The phosphotungstic acid-based solid electrolyte material prepared in this embodiment was tested. (7) The phosphotungstic acid-based solid electrolyte material prepared in this embodiment is placed in a stainless steel mold with a diameter of 10 mm, and cold-pressed under a pressure of 200 MPa for 5 minutes. After demolding, the solid electrolyte sheet is obtained.

[0143] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the phosphotungstic acid-based solid electrolyte material prepared in this embodiment were tested using the same testing method as in Example 1. The test data are detailed in Table 1.

[0144] The solid electrolyte sheets prepared in this embodiment were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0145] Example 3 This embodiment provides a preparation process for a phosphotungstic acid-based solid electrolyte material. The difference from Embodiment 1 lies in the substitution ratio of Al to Zr in step (2). Step (2) specifically involves: under stirring conditions, slowly adding 0.130 g of aluminum nitrate nonahydrate and 0.224 g of zirconium oxychloride octahydrate sequentially to the solution obtained in step (1), wherein Al and [H3PW 11 O40] 2- The molar ratio a is 0.2:1, Zr and [H3PW 11 O40] 2- The molar ratio b was 0.4:1, and the total substitution amount a+b was 0.6. The pH was adjusted to 5.5 with dilute ammonia, and the reaction was continued to be stirred at 80°C for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times with deionized water, and dried under vacuum at 70°C to obtain Al. 3+ and Zr4+ Heterovalent co-skeletal substituent intermediate H 2.5 Al 0.2 Zr 0.4 PW 11.4 O 40 ·2H2O.

[0146] All other steps and parameters are the same as in Example 1.

[0147] The chemical formula of the phosphotungstic acid-based solid electrolyte material prepared in this embodiment is: 0.85[Li 1.5 H 1.5 Al 0.2 Zr 0.4 PW 11.4 O 40 ·2H2O·0.15PEG·0.07 P2O5]+0.15[TA-LLZTO].

[0148] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the phosphotungstic acid-based solid electrolyte material prepared in this embodiment were tested using the same testing method as in Example 1. The test data are detailed in Table 1.

[0149] The solid electrolyte sheets prepared in this embodiment were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0150] To better illustrate the effects of the embodiments of the present invention, a comparative example is provided in the above embodiments.

[0151] Comparative Example 1 The difference between this comparative example and Example 1 is that Al was not performed. 3+ and Zr 4+ A composite material of lithium phosphotungstic acid and PEG was prepared by heterovalent co-framework substitution, without P2O5 interstitial doping, and without oxide solid electrolyte composite. The specific preparation process is as follows.

[0152] (1) Same as step (1) in Example 1, prepare vacant Keggin type [H3PW 11 O 40 ] 2- Solution.

[0153] (2) Do not perform Al 3+ and Zr 4+ Framework substitution was performed by directly vacuum drying the solution obtained in step (1) at 60°C to obtain the vacant Keggin structure H3PW. 12 O 40 ·2H2O solid powder.

[0154] (3) Disperse the solid powder obtained in step (2) in 50 mL of anhydrous ethanol, slowly add 0.096 g of lithium carbonate under stirring at 50 °C, and react for 4 hours; filter, wash 3 times with anhydrous ethanol, and vacuum dry at 60 °C to obtain the lithiation intermediate; wherein, the molar ratio of Li to skeletal substituted phosphotungstic acid is 1.5:1.

[0155] (4) No P2O5 interstitial doping is performed.

[0156] (5) The lithiation intermediate obtained in step (3) is combined with PEG 400 The composite material was obtained by mixing the two materials at a mass ratio of 100:20, and the composite process was the same as in Example 1.

[0157] (6) No mixing of nanoscale oxide solid electrolytes is performed.

[0158] The composite material obtained in step (3) of this comparative example is a solid electrolyte material.

[0159] The solid electrolyte material prepared in this comparative example was placed in a stainless steel mold with a diameter of 10 mm and cold-pressed under a pressure of 200 MPa for 5 minutes. After demolding, the solid electrolyte sheet was obtained.

[0160] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the solid electrolyte material prepared in this comparative example were tested using the same testing methods as in Example 1. The test data are detailed in Table 1.

[0161] The solid electrolyte sheets prepared in this comparative example were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0162] Comparative Example 2 The difference between this comparative example and Example 1 is that only a single Al is performed in step (2). 3+ Replace without adding Zr 4+ The Al substitution amount a is 0.6, and the total substitution amount is the same as in Example 1. The specific process of step (2) in this comparative example is as follows: under stirring conditions, 0.391 g of aluminum nitrate nonahydrate is slowly added to the solution obtained in step (1), wherein Al and [H3PW 11 O40] 2- The molar ratio a was 0.6:1, and the total substitution amount was 0.6. The pH was adjusted to 5.5 with dilute ammonia, and the reaction was continued to be stirred at 80°C for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times with deionized water, and dried under vacuum at 70°C to obtain Al. 3+ Substituted intermediate H 2.5 Al 0.6 PW 11.4O 40 ·2H2O. All other preparation steps are the same as in Example 1.

[0163] The chemical formula of the solid electrolyte material prepared in this comparative example is: 0.85[Li 1.5 H 1.5 Al 0.6 PW 11.4 O 40 ·2H2O·0.15PEG·0.07 P2O5]+0.15[TA-LLZTO].

[0164] The solid electrolyte material prepared in this comparative example was placed in a stainless steel mold with a diameter of 10 mm and cold-pressed under a pressure of 200 MPa for 5 minutes. After demolding, the solid electrolyte sheet was obtained.

[0165] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the solid electrolyte material prepared in this comparative example were tested using the same testing methods as in Example 1. The test data are detailed in Table 1.

[0166] The solid electrolyte sheets prepared in this comparative example were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0167] Comparative Example 3 The difference between this comparative example and Example 1 is that only a single Zr is processed in step (2). 4+ Replace without adding Al 3+ The Zr substitution amount b is 0.6, and the total substitution amount is the same as in Example 1. The specific process of step (2) in this comparative example is as follows: under stirring conditions, 0.336 g of zirconium oxychloride octahydrate is slowly added to the solution obtained in step (1), wherein Zr and [H3PW 11 O40] 2- The molar ratio b was 0.6:1, and the total substitution amount was 0.6. The pH was adjusted to 5.5 with dilute ammonia, and the reaction was continued to be stirred at 80°C for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times with deionized water, and dried under vacuum at 70°C to obtain Zr. 4+ Substituted intermediate H 2.5 Zr 0.6 PW 11.4 O 40 ·2H2O. All other preparation steps are the same as in Example 1.

[0168] The chemical formula of the solid electrolyte material prepared in this comparative example is: 0.85[Li 1.5 H 1.5 Zr0.6 PW 11.4 O 40 ·2H2O·0.15PEG·0.07 P2O5]+0.15[TA-LLZTO].

[0169] The solid electrolyte material prepared in this comparative example was placed in a stainless steel mold with a diameter of 10 mm and cold-pressed under a pressure of 200 MPa for 5 minutes. After demolding, the solid electrolyte sheet was obtained.

[0170] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the solid electrolyte material prepared in this comparative example were tested using the same testing methods as in Example 1. The test data are detailed in Table 1.

[0171] The solid electrolyte sheets prepared in this comparative example were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0172] Comparative Example 4 The difference between this comparative example and Example 1 is that P2O5 was not added for interstitial doping in step (4), and the intermediate obtained in step (3) was directly dispersed in the PEG solution in step (5). The other preparation processes are the same as in Example 1.

[0173] The chemical formula of the solid electrolyte material prepared in this comparative example is: 0.85[Li 1.5 H 1.5 Al 0.3 Zr 0.3 PW 11.4 O 40 ·2H2O·0.15PEG]+0.15[TA-LLZTO].

[0174] The solid electrolyte material prepared in this comparative example was placed in a stainless steel mold with a diameter of 10 mm and cold-pressed under a pressure of 200 MPa for 5 minutes. After demolding, the solid electrolyte sheet was obtained.

[0175] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the solid electrolyte material prepared in this comparative example were tested using the same testing methods as in Example 1. The test data are detailed in Table 1.

[0176] The solid electrolyte sheets prepared in this comparative example were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0177] Comparative Example 5 The difference between this comparative example and Example 1 is that no oxide solid electrolyte was added in step (6), while steps (1) to (5) were the same as in Example 1. The composite material obtained in step (5) was directly used as the solid electrolyte material for relevant tests, and the battery was assembled and tested after cold pressing. The assembly and testing processes were the same as in Example 1, and the test results are detailed in Table 1.

[0178] The solid electrolyte material prepared in this comparative example was placed in a stainless steel mold with a diameter of 10 mm, and cold-pressed at 200 MPa pressure using the same pressure as in Example 1. The pressure was held for 5 minutes, and the solid electrolyte sheet was obtained after demolding.

[0179] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the solid electrolyte material prepared in this comparative example were tested using the same testing methods as in Example 1. The test data are detailed in Table 1.

[0180] The solid electrolyte sheets prepared in this comparative example were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0181] Comparative Example 6 The difference between this comparative example and Example 1 is that the organic plasticizer-lubricant bifunctional component PEG was not added in step (5). Instead, the product obtained in step (4) was directly combined with the nano-scale oxide solid electrolyte in step (6) to obtain the solid electrolyte material. The other steps are the same as in Example 1.

[0182] The solid electrolyte material prepared in this comparative example was placed in a 10mm diameter stainless steel mold and cold-pressed under a pressure of 200MPa for 5 minutes. After demolding, the solid electrolyte sheet was obtained. Comparative example 6 is without PEG lubrication, and the molding difficulty should be much greater than that of example 1. The material without PEG may require higher pressure, but excessive pressure will introduce cracks. Therefore, this comparative example uses the same pressure as example 1 for cold pressing.

[0183] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the solid electrolyte material prepared in this comparative example were tested using the same testing methods as in Example 1. The test data are detailed in Table 1.

[0184] The solid electrolyte sheets prepared in this comparative example were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0185] Comparative Example 7 The difference between this comparative example and Example 1 is that the total substitution amount of Al and Zr in step (2) is 3.0, of which Al substitution amount a is 2.0 and Zr substitution amount b is 1.0. Specifically, step (2) of this comparative example involves: under stirring conditions, slowly adding 1.304 g of aluminum nitrate nonahydrate and 0.560 g of zirconium oxychloride octahydrate sequentially to the solution obtained in step (1), wherein Al and [H3PW 11 O40] 2- The molar ratio a is 2.0:1, Zr and [H3PW 11 O40] 2- The molar ratio b was 1.0:1, and the total substitution amount a+b was 3. The pH was adjusted to 5.5 with dilute ammonia, and the reaction was continued to be stirred at 80°C for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times with deionized water, and dried under vacuum at 70°C to obtain Al. 3+ and Zr 4+ Heterovalent co-skeletal substituted intermediate. Other preparation steps are the same as in Example 1.

[0186] The chemical formula of the solid electrolyte material finally prepared in this comparative example is: 0.85[Li x H (3-x) Al 2.0 Zr 1.0 PW 9.0 O 40 The compound ·2H2O·0.15PEG·0.07P2O5]+0.15[TA-LLZTO], due to excessive substitution, leads to an unstable skeletal structure, and the specific x value is difficult to control precisely.

[0187] The solid electrolyte material prepared in this comparative example was placed in a stainless steel mold with a diameter of 10 mm and cold-pressed under a pressure of 200 MPa for 5 minutes. After demolding, the solid electrolyte sheet was obtained.

[0188] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the solid electrolyte material prepared in this comparative example were tested using the same testing methods as in Example 1. The test data are detailed in Table 1.

[0189] The solid electrolyte sheets prepared in this comparative example were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0190] Comparative Example 8 The difference between this comparative example and Example 1 is that the total substitution amount of Al and Zr in step (2) is lower, which is 0.04, of which Al substitution amount a is 0.02 and Zr substitution amount b is 0.02.

[0191] In this comparative example, step (2) specifically involves: under stirring conditions, slowly adding 0.013 g of aluminum nitrate nonahydrate and 0.011 g of zirconium oxychloride octahydrate sequentially to the solution obtained in step (1), wherein Al reacts with [H3PW 11 O40] 2- The molar ratio a is 0.02.0:1, Zr and [H3PW 11 O40] 2- The molar ratio b was 0.02:1, and the total substitution amount a+b was 0.04. The pH was adjusted to 5.5 with dilute ammonia, and the reaction was continued to be stirred at 80°C for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed three times with deionized water, and dried under vacuum at 70°C to obtain Al. 3+ and Zr 4+ Heterovalent co-skeletal substituted intermediate. Other preparation steps are the same as in Example 1.

[0192] The chemical formula of the solid electrolyte material finally prepared in this comparative example is: 0.85[Li 1.5 H 1.5 Al 0.02 Zr 0.02 PW 11.96 O 40 ·2H2O·0.15PEG·0.07 P2O5]+0.15[TA-LLZTO].

[0193] The solid electrolyte material prepared in this comparative example was placed in a stainless steel mold with a diameter of 10 mm and cold-pressed under a pressure of 200 MPa for 5 minutes. After demolding, the solid electrolyte sheet was obtained.

[0194] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the solid electrolyte material prepared in this comparative example were tested using the same testing methods as in Example 1. The test data are detailed in Table 1.

[0195] The solid electrolyte sheets prepared in this comparative example were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0196] Comparative Example 9 The difference between this comparative example and Example 1 is that in step (5), the mass ratio of polyethylene glycol to intermediate is 40:100, i.e., n=0.40. The other preparation processes are the same as in Example 1.

[0197] The chemical formula of the solid electrolyte material finally prepared in this comparative example is: 0.85[Li 1.5 H 1.5 Al 0.3Zr 0.3 PW 11.4 O 40 ·2H2O·0.40PEG·0.07 P2O5]+0.15[TA-LLZTO].

[0198] The solid electrolyte material prepared in this comparative example was placed in a stainless steel mold with a diameter of 10 mm and cold-pressed under a pressure of 200 MPa for 5 minutes. After demolding, the solid electrolyte sheet was obtained.

[0199] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the solid electrolyte material prepared in this comparative example were tested using the same testing methods as in Example 1. The test data are detailed in Table 1.

[0200] The solid electrolyte sheets prepared in this comparative example were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0201] Comparative Example 10 The difference between this comparative example and Example 1 is that the proportion of the nanoscale oxide solid electrolyte TA-LLZTO is higher in step (6), i.e., α is 0.60. The other preparation processes are the same as in Example 1.

[0202] The chemical formula of the solid electrolyte material finally prepared in this comparative example is: 0.40[Li 1.5 H 1.5 Al 0.3 Zr 0.3 PW 11.4 O 40 ·2H2O·0.15PEG·0.07 P2O5]+0.60[TA-LLZTO].

[0203] The solid electrolyte material prepared in this comparative example was placed in a stainless steel mold with a diameter of 10 mm and cold-pressed under a pressure of 200 MPa for 5 minutes. After demolding, the solid electrolyte sheet was obtained.

[0204] The Young's modulus, relative density, room temperature ionic conductivity, electrochemical window, and lithium-ion transference number of the solid electrolyte material prepared in this comparative example were tested using the same testing methods as in Example 1. The test data are detailed in Table 1.

[0205] The solid electrolyte sheets prepared in this comparative example were used to assemble CR2032 coin cells and tested. The battery assembly and testing process was the same as in Example 1. The test data are detailed in Table 1.

[0206] Table 1 summarizes the test data for Examples 1-3 and Comparative Examples 1-10, as follows.

[0207] Analysis of the test data in Table 1 shows that: Example 1 was compared with Comparative Example 1, which was a completely unmodified phosphotungstic acid-based material containing only PEG organic components, and its room temperature ionic conductivity was only 1.8 × 10⁻⁶. -3 The initial discharge specific capacity was 112.3 mAh / g, and the initial coulombic efficiency was 78.5%. Example 1 shows the effect in Al... 3+ and Zr 4+ The room-temperature ionic conductivity reaches 1.3 × 10⁻⁶ under the combined effects of heterovalent co-substitution, P₂O₅ interstitial doping, and oxide recombination. -2 The S / cm ratio is improved by about an order of magnitude compared to Comparative Example 1, and the initial discharge specific capacity reaches 158.2 mAh / g, an improvement of about 41% compared to Comparative Example 1. The initial coulombic efficiency increases from 78.5% to 92.8%. This is due to the Al... 3+ and Zr 4 + Heterovalent cosubstitution creates lithium vacancies through charge compensation effects, which significantly increases the carrier concentration and enhances the ion conductivity of the material.

[0208] Comparing Example 1 with Comparative Examples 2 and 3, the total substitution amount was the same for all three, a+b=0.6, but Comparative Example 2 used a single Al. 3+ Replacement, comparative example 3 is a single Zr 4+ Replacement. The room temperature ionic conductivity of Example 1 is 1.3 × 10⁻⁶. -2 S / cm, compared to 8.5 × 10 in Comparative Example 2. -3 The S / cm ratio increased by approximately 53%, compared to 7.8 × 10⁻⁶ in Comparative Example 3. -3 The S / cm ratio was improved by approximately 67%. Regarding battery performance, Example 1 exhibited an initial discharge specific capacity of 158.2 mAh / g, representing an improvement of approximately 16% compared to Comparative Example 2's 136.5 mAh / g, and an improvement of approximately 19% compared to Comparative Example 3's 132.8 mAh / g. The lithium-ion transference number of Example 1 was 0.68, significantly higher than Comparative Example 2's 0.58 and Comparative Example 3's 0.55. These data sufficiently demonstrate that Al... 3+ With Zr 4+ The synergistic enhancement effect of heterovalent co-substitution is significantly better than that of single metal substitution systems. Al 3+ Small radius shrinkage effect and Zr 4+ The large radius expansion effect of the Zr-O bonds differentiates the different sites on the Keggin framework, creating a richer and more diverse range of lithium-ion hopping pathways than a single substitution system. At the same time, the stabilizing effect of the Zr-O strong bond on the framework ensures the long-term structural integrity of the ion channels. The performance improvement resulting from the synergy of these three factors far exceeds that of a single substitution.

[0209] Example 1 was compared with Comparative Example 4, which did not include P2O5 for interstitial doping. The room temperature ionic conductivity of Comparative Example 4 was 9.8 × 10⁻⁶. -3 S / cm, in Example 1, the addition of P2O5 increased it to 1.3 × 10⁻⁶. -2 The S / cm ratio was increased by approximately 33%. Regarding battery cycle stability, Comparative Example 4 maintained a capacity retention of 86.5% after 100 cycles, while Example 1 maintained 92.3%, representing an improvement of approximately 5.8 percentage points. This indicates that P2O5 interstitial doping effectively reduces the steric hindrance of ion migration by expanding the interlayer spacing between Keggin units. Simultaneously, its moderate binding effect on water molecules significantly improves the structural stability and environmental adaptability of the material during long-term cycling. Furthermore, although Comparative Example 4 did not contain P2O5, its conductivity was still higher than that of Comparative Examples 2 and 3, demonstrating that Al... 3+ and Zr 4+ Co-substitution itself has already improved ionic conductivity more than Al. 3+ or Zr 4+ Combinations of single substitution and addition of P2O5.

[0210] Example 1 was compared with Comparative Example 5, which did not contain an oxide solid electrolyte. Comparative Example 5 had a room temperature ionic conductivity of 7.2 × 10⁻⁶. -3 The conductivity is S / cm, and the Young's modulus is 41 MPa. In Example 1, the conductivity increased to 1.3 × 10⁻⁶ after the introduction of Ta-LLZTO. -2 The S / cm ratio was increased by approximately 81%, and the initial discharge specific capacity increased from 128.4 mAh / g to 158.2 mAh / g, an increase of approximately 23%. This confirms that the oxide nanoparticles form MO-Al / Zr / W bridging bonds with Keggin-terminal oxygen through their surface oxygen vacancies and Lewis acidic sites, constructing a high-speed ion channel at the interface between phosphotungstic acid and oxides, effectively compensating for the path limitations of single-phase bulk conduction.

[0211] Comparing Example 1 with Comparative Example 6, which did not contain PEG organic components, Comparative Example 6 exhibited a high Young's modulus of 280 MPa, a relative density of only 88.0%, and a room temperature ionic conductivity of 6.5 × 10⁻⁶. -3 S / cm. In Example 1, after the introduction of PEG, the Young's modulus dropped sharply to 80 MPa, a decrease of 71%, while the relative density increased to 94.0% and the electrical conductivity increased to 1.3 × 10⁻⁶. -2S / cm. This fully demonstrates that the PEG amorphous continuous phase coating on the surface and grain boundaries of Keggin nanocrystalline particles effectively isolates direct contact between rigid particles, reducing the overall Young's modulus of the material to a level far below that of traditional oxide electrolytes. Simultaneously, it acts as a solid lubricant during cold pressing, enabling the material to achieve high density at 200 MPa pressure. Comparative Example 6, lacking PEG lubrication, required an pressure of 250 MPa for molding; however, this excessive pressure introduced residual stress and microcracks, resulting in a relative density of only 88.0%, far lower than the 94.0% of Example 1.

[0212] In Comparative Example 7, the total substitution amount of Al and Zr, a+b=3.0, falls under the category of oversubstitution. The room-temperature ionic conductivity of Comparative Example 7 is only 2.1×10⁻⁶. -3 The conductivity decreased by approximately 84%, the electrochemical stability window dropped to 3.8V, the lithium-ion transference number was only 0.38, the initial discharge specific capacity was only 98.5mAh / g, and the capacity retention after 100 cycles was only 62.3%. Compared with Example 1, the conductivity decreased by approximately 84%, the electrochemical window decreased by approximately 27%, and the capacity retention decreased by approximately 32 percentage points. This indicates that excessive heterovalent substitution severely disrupted the charge balance and structural integrity of the Keggin framework. Although the dramatic increase in anionic negative charge created a large number of lithium vacancies, the excessive vacancy defects formed repulsive interactions between vacancies, which in turn disrupted the orderly transport of lithium ions. At the same time, the excessive lattice distortion of the framework led to amorphization and phase separation of the material.

[0213] In Comparative Example 8, the total substitution amount of Al and Zr, a+b=0.04, falls under the category of insufficient substitution. The room-temperature ionic conductivity of Comparative Example 8 is only 2.5×10⁻⁴. -3 Although the Young's modulus remained low (S / cm), the electrical conductivity did not show a significant improvement compared to the unmodified system. This indicates that when the total substitution amount is too low, the synergistic effect between Al and Zr cannot be established, the lithium vacancy concentration created by charge compensation is insufficient, the degree of lattice distortion resulting from the synergistic effect of large and small ions is limited, and the material properties are close to the unmodified level.

[0214] In Comparative Example 9, the PEG content n=0.40, indicating an excess of organic components. The Young's modulus of Comparative Example 9 further decreased to 18 MPa, with a relative density of 96.0%, but its room temperature ionic conductivity was only 3.2 × 10⁻⁶. -3The electrochemical stability window decreased to 4.1V, and the capacity retention after 100 cycles was only 76.5%. Compared with Example 1, although the modulus was lower, the conductivity decreased by about 75%, and the cycle stability deteriorated significantly. This indicates that excessive PEG organic components formed an excessively thick amorphous layer between the particles. Since the intrinsic ionic conductivity of the organic components is much lower than that of the inorganic phase, the excessively thick organic layer significantly increased the interfacial resistance to ion transport. At the same time, the excessive PEG underwent electrochemical side reactions during long-term battery operation, reducing cycle stability.

[0215] In Comparative Example 10, the oxide content α = 0.60, which indicates an excess of oxides. The room temperature ionic conductivity of Comparative Example 10 is 4.1 × 10⁻⁶. -3 The Young's modulus increased significantly to 235 MPa (S / cm), while the relative density decreased to 90.5%. Compared to Example 1, the electrical conductivity decreased by approximately 68%, and the Young's modulus increased by approximately 194%. This indicates that the excessive oxide particles resulted in a relatively insufficient proportion of flexible organic components in the composite material, leading to increased overall material rigidity and deviating from the target of low modulus. Furthermore, the excessive oxide particles introduced a large number of additional interfaces, resulting in significant interfacial impedance.

[0216] In summary, this invention utilizes Al 3+ and Zr 4+ The triple synergistic mechanism of charge compensation effect through heterovalent co-substitution creating lithium vacancies, synergistic lattice distortion between large and small ions enriching ion jumping paths, and strong Zr-O bonds stabilizing the Keggin framework, combined with the layer-expansion effect of P2O5 interstitial doping, the flexible lubrication function of PEG organic components, and the enhanced interfacial conduction of oxide composites, successfully achieved synergistic optimization of ionic conductivity, mechanical flexibility, and cold-pressing formability. 3+ and Zr 4+ Insufficient substitution results in a weak charge compensation effect, failing to effectively increase carrier concentration; excessive substitution, on the other hand, severely impairs ion conduction due to framework structural collapse. Insufficient PEG content prevents the formation of a continuous coating layer, leading to persistently high modulus and molding difficulties; excessive PEG content significantly reduces conductivity due to obstructed interfacial ion transport. Insufficient oxide solid electrolyte content prevents the construction of a continuous long-range interfacial conduction network; excessive oxide content causes the material to lose its low-modulus characteristics due to excessive accumulation of rigid particles. Therefore, the appropriate selection of component ratios and process parameters in this invention is essential to ensure the full realization of the triple synergistic effect and optimal overall performance.

[0217] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A phosphotungstic acid-based solid electrolyte material, characterized in that, The phosphotungstic acid-based solid electrolyte material has a core-shell structure, including: Kernel, for Al 3+ and Zr 4+ Heterovalently co-doped Keggin-type phosphotungstic acid anion nanocrystals; An intermediate transition layer, covering the surface of the core, and comprising the Al 3+ and Zr 4+ Heterovalent co-doping induced charge remodeling region and composition gradient interface; The outer shell functional layer covers the surface of the intermediate transition layer and includes an organic-inorganic hybrid layer in which organic plasticizer-lubricant bifunctional components and oxide solid electrolytes interpenetrate.

2. The phosphotungstic acid-based solid electrolyte material according to claim 1, characterized in that, The general chemical formula of the phosphotungstic acid-based solid electrolyte material is: (1-α)[Li x H (3-x) Al a Zr b PW 12-(a+b) O 40 ·mH2O·nL·zD]+α[Oxide]; Among them, Li x H (3-x) Al a Zr b PW 12-(a+b) O 40 ·mH2O is Al 3+ and Zr 4+ The general chemical formula of heterovalent co-doped Keggin-type phosphotungstic acid anionic nanocrystals is 0.5≤x≤4.0, 0.05≤a≤1.5, 0.05≤b≤1.5, 0.1≤a+b≤2.5, and 0≤m≤8. L is an organic plasticizer-lubricant bifunctional component, and n represents the mass ratio of L to Keggin-type phosphotungstic acid anionic nanocrystals, where 0.05 ≤ n ≤ 0.

3. D represents the interstitial compound, z represents the molar ratio of D to the Keggin-type phosphotungstic acid anionic nanocrystals, and 0.01≤z≤0.3; Oxide represents an oxide solid electrolyte, where 0.05 ≤ α ≤ 0.

5.

3. The phosphotungstic acid-based solid electrolyte material according to claim 2, characterized in that, The particle size Dv50 of the Keggin-type phosphotungstic acid anion nanocrystals is 5nm to 20nm. The organic plasticizer-lubricant bifunctional component includes one or more of polyethylene glycol (PEG), polyethylene oxide (PEO), or polypropylene oxide (PPO); The interstitial compound includes one or more of P2O5, SiO2, or B2O3; The oxide solid electrolyte includes one or more of LATP, LLZO, or TA-LLZTO.

4. The phosphotungstic acid-based solid electrolyte material according to claim 1, characterized in that, The room temperature ionic conductivity of the phosphotungstic acid-based solid electrolyte material is 1×10⁻⁶. -2 S / cm~3×10 -2 S / cm; The Young's modulus of the phosphotungstic acid-based solid electrolyte material is 15 MPa to 130 MPa. The relative density of the phosphotungstic acid-based solid electrolyte material is greater than or equal to 90% under cold pressing pressure of 50 MPa to 250 MPa.

5. A method for preparing a phosphotungstic acid-based solid electrolyte material according to any one of claims 1-4, characterized in that, The preparation method includes: Step S1: Dissolve phosphotungstic acid hydrate in deionized water, adjust the pH to 4.0–6.0, and stir the reaction at 60°C–90°C for 2–6 hours to obtain the vacant Keggin type [H3PW]. 11 O40] 2- Solution; Step S2, add Al-containing solution to the solution obtained in step S1 3+ Soluble salts and Zr-containing 4+ The soluble salt was adjusted to pH 4.5–6.5, and the reaction was carried out at 60–90°C for 4–12 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water, and dried to obtain Al. 3+ and Zr 4+ Heterovalent co-skeletal substituted intermediates; Step S3: Disperse the intermediate obtained in step S2 in a solvent, and add Li-containing... + The soluble salts are reacted at 40℃~80℃ for 2 hours to 8 hours. After the reaction is completed, the mixture is filtered or centrifuged, then washed with deionized water and dried to obtain a lithium-ion partially substituted intermediate. Step S4: Mix the intermediate obtained in step S3 with interstitial compound D, place it in a sealed container, and leave it at room temperature for 12 to 48 hours. Step S5: Combine the product obtained in step S4 with the organic plasticizer-lubricant bifunctional component L to obtain a composite material. Step S6: Mix the composite material with oxide solid electrolyte powder to obtain phosphotungstic acid-based solid electrolyte material; the oxide mass fraction α is 0.05 to 0.

5.

6. The preparation method according to claim 5, characterized in that, The Al-containing 3+ The soluble salts include one or more of aluminum nitrate, aluminum chloride, aluminum acetate, or aluminum sulfate; the Zr-containing salts... 4+ Soluble salts include one or more of zirconium nitrate, zirconium oxychloride, zirconium sulfate, or zirconium acetate; the Al 3+ With the aforementioned [H3PW 11 O40] 2- The molar ratio is a:1, and the Zr 4+ With the aforementioned [H3PW 11 O40] 2- The molar ratio is b:1, where 0.05≤a≤1.5, 0.05≤b≤1.5, and 0.1≤a+b≤2.5; Li + The soluble salts include one or more of lithium carbonate, lithium acetate, lithium nitrate, or lithium hydroxide; the Li + With the aforementioned [H3PW 11 O40] 2- The molar ratio is x:1, where 0.5 ≤ x ≤ 2.5; The interstitial compound D comprises one or more of phosphorus pentoxide, silicon dioxide, or boron trioxide; the molar ratio of D to the lithium-ion partially substituted intermediate is z:1, wherein 0.01≤z≤0.

3.

7. The preparation method according to claim 5, characterized in that, In step S5, the composite process includes: dissolving L in an anhydrous organic solvent to prepare an L solution with a mass fraction of 5% to 20%; dispersing the product obtained in S4 in the L solution; and stirring at room temperature to 60°C for 1 to 4 hours to allow L to wet and adsorb onto the surface and grain boundaries of the product particles. The mass ratio of L to the product obtained in step S4 is 5:100 to 30:

100.

8. The preparation method according to claim 7, characterized in that, Step S5 further includes a ball milling-assisted compounding process, with a ball milling speed of 100 rpm to 400 rpm and a ball milling time of 0.5 hours to 2 hours.

9. The preparation method according to claim 5, characterized in that, In step S6, the mixing methods include: liquid phase dispersion or ball milling-assisted compounding; The liquid phase dispersion method includes: dispersing the oxide solid electrolyte powder in an anhydrous organic solvent, ultrasonically dispersing for 10 to 60 minutes, adding the composite material, stirring for 2 to 8 hours, and then vacuum drying to remove the solvent; The ball milling-assisted compounding process includes: mixing the composite material with oxide powder, and then placing it in a planetary ball mill and ball milling it at a speed of 100 rpm to 400 rpm for 0.5 hours to 4 hours.

10. A fully solid-state lithium battery, characterized in that, It includes a positive electrode, a negative electrode, and a solid electrolyte sheet, wherein the solid electrolyte sheet comprises the phosphotungstic acid-based solid electrolyte material according to any one of claims 1-4, or the phosphotungstic acid-based solid electrolyte material prepared by the preparation method according to any one of claims 5-8.